Real-Time Monitoring of Key Gene Products Involved in Rice Photoperiodic Flowering - Yoshioka, Hayato; Kimura, Keiko; Ogo, Yuko; Ohtsuki, Namie; Nishizawa-Yokoi, Ayako; Itoh, Hironori; Toki, Seiichi; Izawa, Takeshi (Frontiers in Plant Science, 2021)
Flowering is an important biological process through which plants determine the timing of reproduction. Therefore, many plants detect the photoperiod using leaves to forecast seasonal changes and transcribe florigen mRNA at the appropriate time. Translated florigen gene products then move to the shoot apex through vascular tissues to induce floral bud formation. In rice, florigen mRNA is induced more strongly when the day length is shorter than the critical day length through recognition of 30-min differences in the photoperiod. Grain number, plant height, and heading date 7 (Ghd7), which encodes a CCT-domain protein unique to monocots, has been identified as a key floral repressor in rice, and Heading date 1 (Hd1), a rice ortholog of the Arabidopsis floral activator CONSTANS (CO), is another key floral regulator gene. The Hd1 gene product has been shown to interact with the Ghd7 gene product to form a strong floral repressor complex under long-day conditions. However, the mRNA dynamics of these genes cannot explain the day-length responses of their downstream genes. Thus, a real-time monitoring system of these key gene products is needed to elucidate the molecular mechanisms underlying accurate photoperiod recognition in rice. Here, we developed a monitoring system using luciferase (LUC) fusion protein lines derived from the Ghd7-LUC and Hd1-LUC genes. We successfully obtained a functionally complemented gene-targeted line for Ghd7-LUC. Using this system, we found that the Ghd7-LUC protein begins to accumulate rapidly after dawn and reaches its peak more rapidly under a short-day condition than under a long-day condition. Our system provides a powerful tool for revealing the accurate time-keeping regulation system incorporating these key gene products involved in rice photoperiodic flowering.